Lived experiences of inter-urban commercial bus drivers involved in road traffic crashes in Central Region, Ghana. Issue 1 (1st January 2018) - Ojo, Thomas; Agyemang, William; Afukaar, Francis
ABSTRACT: Interurban commercial bus drivers are confronted with inherent risk of over speeding, road curvature, road geometry, and weather condition predisposing them to Road Traffic Crashes (RTCs). Lived experiences of inter-urban commercial bus drivers involved in RTCs in Ghana remains relatively underreported. This relates to their experiences and opinions on the causes of RTCs and the post-experiences as survivors. This paper is an exploratory qualitative study involving face-to-face in-depth interviews with 15 interurban commercial bus drivers who survived RTCs and still drive. The sample was a mix of purposive and snowball sampling techniques at the terminals/stations of interurban commercial bus drivers in Cape Coast, the Capital city of Central Region. The analysis revealed environmental factors (such as weather condition, road surface, road curvature) accounted for the RTCs. Survivors received poor pre-hospital trauma care and no welfare package. Measures to RTCs could include road/transport infrastructure improvements and survivors are to be provided with social welfare package.